Airway Mucus Hypersecretion in Chronic Obstructive Pulmonary Disease Patients: From Basic Pathophysiology to Rehabilitation Approaches - Nazir, Arnengsih; Brandon Clementius (Surabaya Physical Medicine and Rehabilitation Journal, 2025)
Objective: This narrative review aimed to describe the pathophysiology of mucus accumulation and mucus expectoration disorders, rehabilitation assessments, and airway clearance techniques in chronic obstructive pulmonary disease (COPD) patients. Methods: Articles were searched using relevant keywords in PubMed, Google Scholar, and CINAHL databases. Article searches were carried out without limiting the article types or year of publication. Only full-text articles in English and Indonesian were included for data synthesis. Results: COPD causes physiological and structural changes in the airway including stiffness of the airway wall, impaired mucociliary clearance, and decreased cough ability due to respiratory muscle dysfunction. These changes then lead to mucus hypersecretion and mucus accumulation problems resulting in impaired airway clearance and worsened lung function. A rehabilitation assessment is important to assess cough ability and its impact on daily activities and quality of life. Various airway clearance techniques are used to reduce or eliminate airway occlusion and increase expiratory airflow and lung volume. Successful airway clearance can be supported by knowledge of the mechanisms by which mucus accumulates so that appropriate management can be provided. Conclusion: COPD causes airway stiffness, impaired mucociliary clearance, and weakened cough due to respiratory muscle dysfunction, leading to mucus accumulation and worsened lung function. Airway clearance techniques aim to remove obstructions, improve expiratory flow, and enhance lung volume. Understanding mucus accumulation mechanisms is crucial for optimizing airway clearance management based on patient needs.